Development of an object oriented lattice QCD code "Bridge++" - Ueda, S; Aoki, S; Aoyama, T; Kanaya, K; Matsufuru, H; Motoki, S; Namekawa, Y; Nemura, H; Taniguchi, Y; Ukita, N (Journal of physics. Conference series, 2014)
We are developing a new lattice QCD code set "Bridge++" aiming at extensible, readable, and portable workbench for QCD simulations, while keeping a high performance at the same time. Bridge++ covers conventional lattice actions and numerical algorithms. The code set is constructed in C++ with an object oriented programming. In this paper we describe fundamental ingredients of the code and the current status of development.